DEVELOPING FORMULATION STRATEGY AREAS MSMEs BANANA CHIPS BASED ON SUPERIOR COMMODITIES IN INHIL COUNTY - Nofrizal Nofrizal (Fakultas Ekonomi dan Bisnis Islam Universitas Islam Negeri Sumatera Utara, 2017)
Purpose this research to help district Indragiri Hilir Riau Province to arrange development strategy area of Micro, Small and Medium Enterprises (MSMEs) banana Chips, so that they can increase income civil society there with using benefit of their superior commodity area and another area doesn't have it. The resource of information in this research using interviews and observation method and to arranging development strategy analysis we use the SWOT analysis-24 k it was development from SWOT analysis-4 k, it have function to clearly business position and using it as competitive strategy for creating and formulate development strategy. Result of this research showed that strategy development of MSMEs banana chips district Indragiri Hilir is turnaround strategy with using government fund and making program national banana chips event